Digitalisasi yang berkembang semakin pesat membawa dampak signifikan terhadap karakter remaja, di mana pengaruh teknologi dan media social dapat membentuk perilaku maupun identitas diri remaja. Kegiatan penelitian ini bertujuan untuk memaknai karakter rem - Dliyaul Latifa; Lindya Rossita Handoko; M. Sifa’urrohman; Kholifatus Sholihah (Nawasena Bhakti, 2025)
Rapidly growing digitalization has a significant impact on adolescent character, where the influence of technology and social media can shape adolescent behavior and self-identity. the activities of this study have the intention to interpret the character of adolescents in the digital era as well as to see the duties of parents, schools, and the surrounding environment in facing the challenges of digitalization. The methods used include socialization, training, and evaluation conducted in coordination with Saka Wirakartika Jatirogo. The results of this study found that there are still many parents who pay less attention to their children's activities in the use of technology. In addition, many teenagers feel that they have lost their direction and identity due to the negative influence of social media. It can be concluded that this socialization emphasizes the importance of the duties of parents, schools, and the surrounding environment in assisting adolescents to face the digital era, which aims to avoid the negative impact of technology while forming positive, supportive, and environmentally sensitive characters. Thus, collaboration between families, educational institutions and communities is key in developing adaptive and resilient adolescent characters in the midst of rapid digitalization.